IFN-γ plays a detrimental role in murine defense against nasal colonization of Staphylococcus aureus - Satorres, Sara Elena (2009)
The anterior nares are the major reservoir in humans of Staphylococcus aureus with the risk of developing endogenous infections or transmitting infections to susceptible persons. The mechanisms that mediate attachment of staphylococci to the nasal mucosa are little known. The purpose of the present work was to study some factors that could influence the nasal colonization in an animal model of mice. We investigated the possible role of IFN-γ. We used S. aureus ATCC 35556 (SA113) slime-producing and ATCC 25923 non-slime-producing strains. Male 6-week-old BALB/c, C57BL/6 (wild-type, WT), and gene-deficient IL-12p40 (IL-12p40-/-) or IL-4 (IL-4-/-) mice on C57BL/6 background were infected with a dose of S. aureus of 106 CFU in 10 μl of saline. The total number of S. aureus CFU per nose and lung, specific IgA response and IFN-γ levels were evaluated. Significant higher CFU were recovery from the narines of C57BL/6 compared with BALB/c mice either after ATCC 35556 (p < 0.0001) and ATCC 25923 (p < 0.02) strain infection. Low IgA response correlated with high bacterial counting in the C57BL/6 nasal region. Moreover, C57BL/6 mice showed major colonization of slime-producing S. aureus ATCC 35556 than non-slime-producing ATCC 25923 S. aureus strain (p < 0.02). IL-12p40-/-mice clarified the bacteria from their nose more efficiently that WT mice after slime-producing S. aureus (p < 0.0001). Accordingly, significant lower level of IFN-γ were detected in IL-12p40-/- compared with WT mice after infection with this strain (p < 0.03). The results suggested the influence of the slime production in nasal colonization of S. aureus, and indicate at first time that IFN-γ may play a detrimental role in this mucosal infection. These results could contribute to elucidate mucosal immune mechanisms involved in S. aureus colonization and then control infections in susceptible persons.